Wegner, J. - The Sunshade Chapel of Meritaten from the House-of-Waenre of Akhenaten - García Martínez, Rocío (ISIMU, 2019)
Wegner, J. The Sunshade Chapel of Meritaten from the House-of-Waenre of Akhenaten University of Pennsylvania Museum of Archaeology & Anthropology, Philadelphia,2017 184 pp ISBN 1934536873 € 49.57.